PENGARUH TEKANAN ANGGARAN WAKTU SEBAGAI VARIABEL MODERASI TERHADAP HUBUNGAN ANTARA FAKTOR INDIVIDU DAN KUALITAS AUDIT - Jefry Gasperz (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2014)
This study examines the effect of time budget pressure as a moderating variable on the relationship between individual factors, namely accountability, ethical awareness, and auditor independence and audit quality on BPK Representative Maluku province. Respondents are auditors working on BPK RI Representative Maluku Province. Population are42 respondents, but only 34 respondents who returns quesionary and can be used in data processing. The sampling method used is census sampling. Data processing is performed using moderated regression analysis (MRA) and assisted by SPSS version 17.0. The results showed that time budget pressure to moderate the relationship between accountability and audit quality as well as moderate the relationship between ethical awareness and the audit quality, but time budget pressure has not influence moderate therelationof auditor independence and audit quality. Keywords: accountability, ethical awareness, auditor independence, time budget pressure, audit quality